2023
DOI: 10.3390/ijms24021086
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction: The Hidden Player in the Pathogenesis of Atherosclerosis?

Abstract: Atherosclerosis is a multifactorial inflammatory pathology that involves metabolic processes. Improvements in therapy have drastically reduced the prognosis of cardiovascular disease. Nevertheless, a significant residual risk is still relevant, and is related to unmet therapeutic targets. Endothelial dysfunction and lipid infiltration are the primary causes of atherosclerotic plaque progression. In this contest, mitochondrial dysfunction can affect arterial wall cells, in particular macrophages, smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 113 publications
0
24
0
Order By: Relevance
“…Interestingly, a decrease of mtDNA copy number is proven to lead to endothelial cell dysfunction, which is a characteristic of early events occurring in the pathogenesis of atherosclerosis. 57 Although we established an infection model with viable P. gingivalis and found that P. gingivalis induced mitochondrial dysfunction, we did not further confirm which virulence factor of P. gingivalis was responsible. It is well-accepted that gingipains, LPS, peptidoglycan and flagellin are fundamental virulence factors for P. gingivalis.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Interestingly, a decrease of mtDNA copy number is proven to lead to endothelial cell dysfunction, which is a characteristic of early events occurring in the pathogenesis of atherosclerosis. 57 Although we established an infection model with viable P. gingivalis and found that P. gingivalis induced mitochondrial dysfunction, we did not further confirm which virulence factor of P. gingivalis was responsible. It is well-accepted that gingipains, LPS, peptidoglycan and flagellin are fundamental virulence factors for P. gingivalis.…”
Section: Discussionmentioning
confidence: 85%
“…mtDNA is more vulnerable to ROS attack when exposed to oxidative damage than nuclear DNA. Interestingly, a decrease of mtDNA copy number is proven to lead to endothelial cell dysfunction, which is a characteristic of early events occurring in the pathogenesis of atherosclerosis 57 …”
Section: Discussionmentioning
confidence: 99%
“…This accumulation of reactive oxygen species likely plays a prominent role in the development of atherosclerosis, as demonstrated by numerous studies. [52][53][54][55][56][57] Another phenomenon could have an impact, which is the release by activated monocytes of free mitochondria and microvesicles containing mitochondrial elements, as demonstrated by Puhm et al 58 The development of therapeutic interventions to limit this mitochondrial dysfunction and its impact on cardiovascular risk could be contemplated in patients with T2D, as is already the case in psychiatric 59 or neurological diseases. 60 Nevertheless, our study puts monocytes at the core of the equation for the heightened risk in patients with T2D and advocates for further research on antiatherosclerotic treatments targeting monocytes and mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are highly dynamic organelles undergoing coordinated cycles of fission and fusion, so called mitochondrial dynamic, which is fundamental for the organelle function 75 . We found that MTF2, mitochondrial protein responsible for fusion process, expression was reduced by ethanol consumption with no difference in DRP1 (mitochondria fission inducer), interestingly losartan prevented these changes, suggesting ethanol decreases mitochondria fusion via RASS activation.…”
Section: Discussionmentioning
confidence: 99%